PENINGKATAN KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 1 BANGUN PURBA DENGAN MODEL PROBLEM BASED LEARNING MELALUI MEDIA GAMBAR - Herta Sirait (Universitas Wijaya Kusuma Surabaya, 2023)
The Problem Based Learning using image can be used to improve the ability to write news text, because these models and media provide ideas for students to find and stort activities to write news teks. New text writing activities in the good practice process carried out by the author have shown an increase in news text writing skillnews text.